Optical generation of electron–hole pairs in phosphor and boron co‐doped Si nanocrystals in SiO2. Issue 11 (3rd November 2016) - Chung, Nguyen Xuan; Limpens, Rens; Lesage, Arnon; Fujii, Minoru; Gregorkiewicz, Tom
Abstract: We investigated experimentally optical generation of electron–hole pairs in layers of silicon nanocrystals co‐doped with phosphor and boron, dispersed in a solid‐state matrix of silicon dioxide. The study was performed at room temperature. From the red‐shift of the photoluminescence spectrum and the enhanced absorption at low energies appearing upon doping, the formation of additional levels inside the bandgap has been confirmed. By comparing the transient induced absorption at two excitation energies, below and well above twice the emission energy, the evidence of carrier multiplication in co‐doped silicon nanocrystals has been obtained for the first time. Effect of doping on optical characteristics of silicon nanocrystals